Reproducción del rana hvla labialis (1962)
1. Oögenesis of the frog, Hyla labialis has been studied in order to Compare it with the same process in frogs which live in countries with definite climatic seasons. Fertilized eggs can be obtained after pituitary injection during the months of October through June and occasionally during the rest of the year. 2. Whole oöcytes were measured and counted in samples taken from mature ovaries, immature ovaries and ovaries after ovulation had taken place. There are oöcytes of all sizes present in mature ovaries; in immature ovaries and ovaries after ovulation there are cells of all sizes up to 1.200 mm. diameter. 3. In sections of ovaries, the diameter of the cells, of the nuclei and of the yolk platelets was measured. The cytological changes in the nuclei and cytoplasm were studied. Yolk platelets first appear in cells which have a diameter of 0.350 to 0.400 mm. Melanin is first found in cells of 0.700 mm. or more in diameter. In general, the cytological changes are similar to those described by other investigators for other species. 4. The most obvious and interesting difference between oögenesis in Hvla labialis and other species previously studied is the presence of oöcytes of all sizes and in large quantities in the ovaries studied immediately after ovulation occured. The results reported in this paper suggest that oögenesis is a continuous process throughout the entire year here in Bogotá, Colombia. In this respect it differs from that described for amphibians which live in countries with definite climatic seasons in which the growth of oöcytes is a discontinuous process and takes place in distinct groups of cells developing simultaneously.